2016
DOI: 10.3109/0886022x.2016.1158070
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of propolis on methotrexate-induced kidney injury in the rat

Abstract: Objectives Propolis is a potent antioxidant and a free radical scavenger. Pharmacological induction of heat shock proteins (HSPs) has been investigated for restoring normal cellular function following an injury. In this study, effect of propolis on HSP-70 expression in methotrexate-induced nephrotoxicity and direct preventive effect of propolis in this toxicity were investigated. Material and methods A total of 40 male Wistar albino rats were divided into four groups: Group 1 was the untreated control. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…The increased level of its cellular metabolites could induce oxidative and inflammatory tissue damages [ 37 ], which could be demonstrated in the form of histopathological changes [ 38 ] and elevation of serum liver enzymes [ 39 ]. Moreover, MTX metabolites were found to precipitate in renal tubules, causing marked nephrotoxicity in rats [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased level of its cellular metabolites could induce oxidative and inflammatory tissue damages [ 37 ], which could be demonstrated in the form of histopathological changes [ 38 ] and elevation of serum liver enzymes [ 39 ]. Moreover, MTX metabolites were found to precipitate in renal tubules, causing marked nephrotoxicity in rats [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Propolis has also been found to be effective in protecting against methotrexate-induced kidney injury in rats 227 . The effect of propolis on mitochondrial biogenesis in CKD remains to be determined.…”
Section: Nutrients That Target Mitochondrial Dysfunctionmentioning
confidence: 99%
“…In addition, we suggest that a more detailed analysis, including dosage, duration and timing of administration also should be performed. Furthermore, we also speculated that there was the possibility that crude honey, including various honey products such as propolis and bee pollen, is more closely associated with nephroprotective effects more than pure RJ because these products exert protective effects on kidney function [ 61 , 62 ]. Indeed, as mentioned above, animal experiments also showed that the nephroprotective effects of RJ were lower than those of honey [ 49 ].…”
Section: Activity Of Royal Jelly Against Cancer Therapy-induced Tomentioning
confidence: 99%